Как доказать тождество -0.2x³(2,5x-4)(6-x²)= 0,5x^6-0,8x^5-3x⁴+4,8x³

doggibou doggibou    2   14.04.2021 13:36    0

Ответы
Raptords Raptords  14.04.2021 13:40

1) f(x)=2x³-4x²   x₀=-1

yk=y(x₀)+y`(x₀)*(x-x₀)

y(x₀)=2*(-1)³-4*(-x)²=-2-4=-6

y`(x₀)=6x²-8x=6*(-1)²-8*(-1)=6+8=14  ⇒

yk=-6+14(x-1)=-6+14x-14=14x-20.

2) y`=(3x²+2)/√x)`=(6x*√x-(3x²+2)*(1/2*√x))/x=√х(4.5-1/х²).

3) f`(x)=(6x-x*√x)`=0   ОДЗ: x≥0

-1,5*√x+6=0

√x=4

x=16

0+16-+∞

x∈[0;16).

Объяснение:

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра